MRI of cardiovascular malformations - Kastler, Bruno (Springer, 2011)
MRI is a non-invasive and non-ionizing imaging modality that is perfectly suited for the diagnosis and follow-up of both pediatric and adult congenital heart disease. It provides a large field of view and has the unique ability to depict complex cardiac and vascular anatomy and to measure cardiac function and flow within one examination. MRI is the ideal complement to echocardiography whenever the information provided by the latter is limited. This book has been conceived as a self-teaching manual that will assist qualified radiologists, cardiologists, and pediatricians, as well as those in training. It is richly illustrated with numerous images and drawings that cover all usual and most unusual anomalies. The principal author, Professor Bruno Kastler, is head of radiology at Besançon University Hospital, France and is board certified in both radiology and cardiology.